The best interest’s principle as an indeterminate legal concept and its concretion in the national jurisprudence. - Herencia Espinoza, Silvia Jenifer (2021)
The application of the principle of the best interests of the child, as a statement of mandatory application, dates to the Children’s Convention; Due to its abstract nature, it has required that in our country a regulation be issued that determines the application parameters, in order to justify the adoption of measures that are the most satisfactory for the integral development of the minor.  Although this principle has been incorporated in the jurisdictional decisions, the interpretation to which it is arriving turns out to be still very broad, without making an adequate weighting between the possible solutions, in order to establish which of them turns out to be the most convenient for the minor.